Prototipe Papan Trainer PLC Sederhana Berbasis Arduino Uno Dengan Menggunakan Software Outsel Studio - Rio Candra Azhari Valdy; Zaenal Abidin (Jurnal JEETech, 2023)
PLC practicum is needed to support electrical engineering graduate students as a provision of experience operating PLC. To support the needs of PLC trainers in the electrical engineering laboratory at Universitas Islam Lamongan (Unisla), it is necessary to conduct a study that exploit the Arduino Uno as a control controller by making a prototype of a simple PLC trainer board based on the Arduino Uno using out seal Studio software. On the testing tool, the author uses an example of a logic gate ladder which then the ladder diagram will be created in the studio out seal software then will be uploaded to the Arduino Uno PLC and will be run on the trainer. In the mechanism, this tool uses an Arduino Uno microcontroller as a control center, an opt coupler circuit as a voltage separator between the input voltage and voltage on the Arduino, a relay opt coupler circuit as a voltage separator and an Arduino output voltage amplifier which is then flowed to the load. Switches, push buttons, and infrared sensors are used as examples of PLC input sensors. Red, yellow, green lights and 220v buzzers are used as output indicators as well as load examples. Conclusion on the experiment Arduino Uno PLC logic gate can work normally when operated